Case Report: Rudimentary Horn Pregnancy - Greenwood González, Eric (2021)
Rudimentary horn pregnancy is a rare disease, making early diagnosis difficult for the attending physician. Rudimentary horn rupture is a life-threatening complication for the mother, clinical suspicion, early diagnosis, and timely early intervention are essential to avoid this complication. We present the case of a patient with a unicornate uterus with a rudimentary horn pregnancy.   Key words: unicornate uterus; pregnancy; rudimentary horn; Müllerian malformation